2012
DOI: 10.5402/2012/978709
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fermentation on Physicochemical Properties and Oxalate Content of Cocoyam (Colocasia esculenta) Flour

Abstract: The effect of fermentation on physicochemical properties and oxalate content of cocoyam (Colocasia esculenta) flour was evaluated. The cocoyam, white flesh was cleaned, washed, peeled, sliced into chips of 2-2.5 cm thickness, soaked in tap water and left to ferment for 24 h and 48 h. The fermented cocoyam was then drained, dried in cabinet dryer at 60• C for 24 h and milled. The flour samples were passed through a 45 µm mesh size sieve. Unfermented cocoyam flour was also produced and served as a control. Calci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 12 publications
3
17
1
2
Order By: Relevance
“…The degree of viscosity reduction during heating process is termed as breakdown viscosity (BV); and can be used as an indicator for pasting stability during heating and stirring [20] [21].…”
Section: Pasting Properties Of Corn Flours After 36 Hours Of Fermentamentioning
confidence: 99%
“…The degree of viscosity reduction during heating process is termed as breakdown viscosity (BV); and can be used as an indicator for pasting stability during heating and stirring [20] [21].…”
Section: Pasting Properties Of Corn Flours After 36 Hours Of Fermentamentioning
confidence: 99%
“…Boiling causes considerable cell rupture and facilitate the leakage of soluble oxalate into cooking water and all observed the same trend [16], [49], [53], [54], [55], [56].Fermentation decreased the oxalate concentration significantly. Oke and Bolarinwa [57] reported that the 65% reduction of oxalates of taro was observed in 48 hours of fermentation and similar studies showed a decrease in oxalate content in fermentation process [28], [42]. Treatment process done prior to frying like washing, peeling, dicing as well as soaking could reduce the oxalate concentration.…”
Section: Phytatementioning
confidence: 99%
“…This could probably be due to the various quantity of seedless breadfruit leaf powder in the blends. These increases in swelling indices of millet, pigeon pea flour and their blends as the fermentation time increases, made the bond relax, thereby causing starch granules to imbibe water in swell and a low molecular weight amylase solubilize and leach out into the aqueous medium (Oke and Bolarinwa, 2012).…”
Section: Effect Of Fermentation Of the Functional Properties Of The Smentioning
confidence: 99%